Intraflagellar transport trains and motors: Insights from structure. (November 2020) - Webb, Stephanie; Mukhopadhyay, Aakash G.; Roberts, Anthony J.
Abstract: Intraflagellar transport (IFT) sculpts the proteome of cilia and flagella; the antenna-like organelles found on the surface of virtually all human cell types. By delivering proteins to the growing ciliary tip, recycling turnover products, and selectively transporting signalling molecules, IFT has critical roles in cilia biogenesis, quality control, and signal transduction. IFT involves long polymeric arrays, termed IFT trains, which move to and from the ciliary tip under the power of the microtubule-based motor proteins kinesin-II and dynein-2. Recent top-down and bottom-up structural biology approaches are converging on the molecular architecture of the IFT train machinery. Here we review these studies, with a focus on how kinesin-II and dynein-2 assemble, attach to IFT trains, and undergo precise regulation to mediate bidirectional transport.